Studi Literatur Riset Management Control For Sustainability 2010-2019 - Se Tin Se Tin; Santy Setiawan; Yunita Christy (Universitas Pamulang, 2021)
Abstract The purpose of this paper is to review management control for sustainability research for the period 2010-2019. This study applied a descriptive approach to answer about the motivation (research objectives), the theory; the research method used; research findings and research agenda. Management control for sustainability research development was traced through article published in Schimago journal rank (SJR) namely Management Accounting Research dan Journal of Management Accounting Research. The unit of analysis is a journal containing articles management accounting issues and sustainability issues. A total of 344 articles were examined that resulted in 6 articles for analysis. Some findings are, first, research into sustainability control systems focused on environmental sustainability; discuss the role of management control systems in managing social responsibility strategies; and examine the relationship between external pressures and sustainability control systems. Second, the theories used are configuration theory, institutional theory, institutional logic, the framework of the four control levers, the environmental management control system; third, quantitative, qualitative, and content analysis methods are used in research; fourth, generally analysis at managerial level; fifth, using primary data and secondary data. Keywords: Sustainability; Management Control System Abstrak Tujuan studi ini adalah meninjau riset pengendalian manajemen untuk keberlanjutan pada periode 2010-2019. Studi ini menerapkan pendekatan deskriptif untuk menjawab tentang motivasi (tujuan penelitian), teori, metode penelitian yang digunakan, temuan penelitian dan agenda penelitian. Riset pengendalian manajemen untuk keberlanjutan ditelusuri melalui artikel yang diterbitkan dalam Schimago journal rank (SJR) yaitu Management Accounting Research dan Journal of Management Accounting Research. Unit analisis adalah artikel topik akuntansi manajemen dan isu keberlanjutan. Sebanyak 344 artikel diperiksa dan diperoleh 6 artikel untuk direviu. Beberapa temuan adalah, pertama, penelitian tentang sistem kontrol keberlanjutan fokus pada kelestarian lingkungan; membahas peran sistem kontrol manajemen dalam mengelola strategi tanggung jawab sosial; dan menguji hubungan antara tekanan eksternal dengan sistem kontrol keberlanjutan. Kedua, teori yang digunakan adalah teori konfigurasi, teori kelembagaan, logika kelembagaan, kerangka kerja dari empat tuas kontrol, sistem kontrol manajemen lingkungan; ketiga, metode analisis kuantitatif, kualitatif, dan analisis konten digunakan dalam penelitian; keempat, umumnya analisis pada tingkat manajerial; kelima, menggunakan data primer dan data sekunder. Kata kunci: Keberlanjutan; Sistem Pengendalian Manajemen